The siren song - Ursu, Anne. (New York : Atheneum Books for Young Readers, 2007)
Thirteen-year-old Charlotte must rescue humankind again when the evil Philonecron captures her cousin Zee, and Poseidon himself sends a sea monster to eat the cruise ship on which Charlotte's parents are trapped.
Keywords: Adventure and adventurers -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Poseidon (Greek deity) -- Juvenile fiction; Animals, Mythical -- Juvenile fiction; Fantasy fiction; Adventure fiction